Formação em psiquiatria de ligação no internato de psiquiatria. - A Barbosa; J S Gago (Acta Médica Portuguesa, 1997)
The development of consultation-liaison psychiatry in Portuguese general hospitals raises the need for specific training to be included in the preparation of psychiatric trainees. In order to contribute to a better quality of liaison psychiatric training we propose guidelines for this training period. We describe the aims of a training period, the core curriculum, the structure of this training and provide a bibliography. We also propose a systematic evaluation profile for psychiatric trainees and supervisor.